Teomística: um diálogo entre experiência mística e a fenomenologia à luz da teologia fundamental - Anéas, André (2023)
Theomistics is a hermeneutic-theological key based on three extensive areas. The history, especially of Christianity, immersed in signals about the mystical element, explicitly in the mystics (compiled as a mystical corpus); theology, using the negative theology proposal of Vladimir Lossky (Eastern tradition), the understanding of Christian humanism by Pope Francis, Rubem Alves, and José M. Castillo, and the understanding of the romantic F. Schleiermacher, who understands that the essence of religion is gefühl; and sociological and philosophical, understanding the socio-religious roles of the priest, the prophet, and the mystic in the religious phenomenon, the postmodern philosophy of Gianni Vattimo with his pensiero debole, and the Phenomenology of Life by Michel Henry. Aiming to oppose a fundamentalist theological work, of maintenance of the religious status quo, produced in a violent and epistemologically superb Christianity, enemy of secularization and postmodernity that rationalizes the experience of God, the theomistic, in this dialogue between mystics, hermeneutics and phenomenology, propose a theological wisdom, which is built from seven interdependent principles: an epistemology of the possible; an apophatic imperative; the mystical a priori, resulting from the analysis of the characteristics of the mystical corpus; overcoming the dichotomy between theology and praxis; trivializing the mystical experience; profanation of the sacred and sacralization of the profane; and Life as the ultimate mystery of experience. This theological wisdom, relativizing the theological, proposes a de-romanticized theology, capable of considering the experience of God as the radical foundation of its hermeneutic proposal, perpetuating the Mystery as a mystery and comprehensively influencing the theological work